Biomarkers for the adverse effects on respiratory system health associated with atmospheric particulate matter exposure - Guo, Caixia; Lv, Songqing; Liu, Yufan; Li, Yanbo (Journal of hazardous materials, 2022)
Large amounts of epidemiological evidence have confirmed the atmospheric particulate matter (PM2.5) exposure was positively correlated with the morbidity and mortality of respiratory diseases. Nevertheless, its pathogenesis remains incompletely understood, probably resulting from the activation of oxidative stress, inflammation, altered genetic and epigenetic modifications in the lung upon PM2.5 exposure. Currently, biomarker investigations have been widely used in epidemiological and toxicological studies, which may help in understanding the biologic mechanisms underlying PM2.5-elicited adverse health outcomes. Here, the emerging biomarkers to indicate PM2.5-respiratory system interactions were summarized, primarily related to oxidative stress (ROS, MDA, GSH, etc.), inflammation (Interleukins, FENO, CC16, etc.), DNA damage (8-OHdG, γH2AX, OGG1) and also epigenetic modulation (DNA methylation, histone modification, microRNAs). The identified biomarkers shed light on PM2.5-elicited inflammation, fibrogenesis and carcinogenesis, thus may favor more precise interventions in public health. It is worth noting that some inconsistent findings may possibly relate to the inter-study differentials in the airborne PM2.5 sample, exposure mode and targeted subjects, as well as methodological issues. Further research, particularly by -omics technique to identify novel, specific biomarkers, is warranted to illuminate the causal relationship between PM2.5 pollution and deleterious lung outcomes. [Display omitted] •Airborne particulate matter pollution is a global issue for public health.•PM exposure is a risk factor for respiratory diseases.•Biomarkers indicating PM-respiratory system interactions was detailed introduced.•PM components serve as the key attributors to the adverse respiratory outcomes.